ANALISIS PENERAPAN MODEL UTAUT (UNIFIED THEORY OF ACCEPTANCE AND USE OF TECHNOLOGY) TERHADAP PERILAKU PENGGUNA SISTEM INFORMASI (STUDI KASUS: SISTEM INFORMASI AKADEMIK PADA STTNAS YOGYAKARTA) - Trie Handayani; Sudiana Sudiana (Angkasa: Jurnal Ilmiah Bidang Teknologi, 2017)
The appears of the popularity of web technologies and applications have created a vast opportunity for organizations, including institutions of higher education. With the presence of Academic information systems (SiAkad) that is in STTNAS, then do some research to find out the intention of the behavior in the use of Academic information systems using the UTAUT model (Unified Theory Of Acceptance And Use Of Technology). The phenomenon underlying this study is: not yet optimal use of Academic information systems by civitas academic (professors, students and employees) in the process of learning and socializing, so the existence of maximal and haven't yet SiAkad his crisp utilization impact of its use for the entire civitas academic. The study was limited in its scope: the analysis of the influence of Performance Expextancy, Expextancy Effort, Social Influence and Facilitating Condition against the intention SiAkad usage behavior in STTNAS in Yogyakarta. The data in the study on the test with the SEM analysis tool (Structural Equation Modeling). SEM is a tool of statistical analysis that are used to complete the research of multilevel models simultaneously. SEM can be used to solve equations with variables that make up the path. Research results based on the analysis and discussion is a variable PerformanceExpectancy (PE), Social Influence (SI) and Facilitating Condition (FC) effect significantly to Behavioral Intention, while variable Effort Expectancy (EE) provides results that are not significant. Fourth overall Predictor is only able to explain the impact on behavioral intention of 37,6 percent.